2021
DOI: 10.1371/journal.pone.0260548
|View full text |Cite
|
Sign up to set email alerts
|

A common variant of CNTNAP2 is associated with sub-threshold autistic traits and intellectual disability

Abstract: Sub-threshold autistic traits are common in the general population. Children with sub-threshold autistic traits have difficulties with social adaptation. Contactin-associated protein-like 2 (CNTNAP2) is associated with the development of Autism spectrum disorder (ASD) and the single-nucleotide polymorphism rs2710102 (G/A) of CNTNAP2 is suggested to contribute to sub-threshold social impairments and intellectual disabilities. We recruited 67 children with Autistic disorder (AD) (49 boys, 18 girls, aged 38–98 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…5 Moreover, we recently investigated children without apparent delay and reported that the A-allele of this SNV was significantly more frequent in children with ASD than in children with typical development (TD), and the A-allele was associated with more autistic traits among children with TD. 6 It was speculated that the A-allele of rs2710102, which is frequent in ASD, may be associated with lower receptive language ability, which explains the lag between expressive and receptive language abilities in this population. However, it remains unclear whether this association is present in individuals without language delay, regardless of whether they had ASD or TD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Moreover, we recently investigated children without apparent delay and reported that the A-allele of this SNV was significantly more frequent in children with ASD than in children with typical development (TD), and the A-allele was associated with more autistic traits among children with TD. 6 It was speculated that the A-allele of rs2710102, which is frequent in ASD, may be associated with lower receptive language ability, which explains the lag between expressive and receptive language abilities in this population. However, it remains unclear whether this association is present in individuals without language delay, regardless of whether they had ASD or TD.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, rs2710102, an SNV in CNTNAP2 , is associated with lower receptive language ability in individuals with ASD who had language delay 3 as well as in individuals with specific language impairment 5 . Moreover, we recently investigated children without apparent delay and reported that the A‐allele of this SNV was significantly more frequent in children with ASD than in children with typical development (TD), and the A‐allele was associated with more autistic traits among children with TD 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The singlenucleotide polymorphism of CNTNAP2 is suggested to contribute to epileptic seizures and intellectual disabilities. (Shiota et al 2021) Current literature on the frequencies of these polymorphisms in different populations and their relation with co-occurrence of intellectual disability and epilepsy is still unclear. Therefore, the biological role of the CNTNAP2 gene in neurodevelopmental disorders is currently a study focus area.…”
Section: Introductionmentioning
confidence: 99%
“…The single-nucleotide polymorphism of CNTNAP2 is suggested to contribute to epileptic seizures and intellectual disabilities. (Shiota et al 2021) Current literature on the frequencies of these polymorphisms in different populations and their relation with co-occurrence of intellectual disability and epilepsy is still unclear. Therefore, the biological role of the CNTNAP2 gene in neurodevelopmental disorders is currently a study focus area.…”
Section: Introductionmentioning
confidence: 99%